1973
DOI: 10.1126/science.180.4086.645
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Lithium Administration: Effects on the Brain's Serotonergic Biosynthetic Systems

Abstract: Short-term treatment with lithium chloride stimulates the uptake of tryptophan and its conversion to serotonin by striate synaptosomes. Preincubation of striate synaptosomes with L-tryptophan and in vivo administration of L-tryptophan appear to act in a similar manner. Midbrain tryptophan hydroxylase activity is reduced in temporal continuity with the lithium-induced activation of tryptophan uptake and conversion. By 10 days, conversion of tryptophan to serotonin in nerve endings becomes a joint function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0
1

Year Published

1974
1974
1989
1989

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(37 citation statements)
references
References 18 publications
7
29
0
1
Order By: Relevance
“…As for NE transmis sion, it has been suggested that the increase in NE turnover observed after short-term lith ium administration is followed several weeks later by a relatively steady state [8]. The observed increase in 5-HT brain levels after 21-day lithium administration is in agree ment with previous reports showing in creases in 5-HT synthesis by as much as 80% [6,20], It has been suggested [11,12,15,22] that short-term administration of lithium in creases 5-HT synthesis by increasing precur sor uptake, and that continued lithium ad ministration, after 10-21 days, leads to a compensatory decrease in tryptophan hy droxylase activity which eventually brings 5-HT synthesis back to a normal, although 'buffered', state. Since our brain assays were performed on the 21st day, it is difficult to say if the small, although significant, 20% increases in 5-HT levels represent a phase in the gradual return from increased to normal levels, or if it reflects the attainment of steady higher baseline levels.…”
Section: Discussionsupporting
confidence: 81%
“…As for NE transmis sion, it has been suggested that the increase in NE turnover observed after short-term lith ium administration is followed several weeks later by a relatively steady state [8]. The observed increase in 5-HT brain levels after 21-day lithium administration is in agree ment with previous reports showing in creases in 5-HT synthesis by as much as 80% [6,20], It has been suggested [11,12,15,22] that short-term administration of lithium in creases 5-HT synthesis by increasing precur sor uptake, and that continued lithium ad ministration, after 10-21 days, leads to a compensatory decrease in tryptophan hy droxylase activity which eventually brings 5-HT synthesis back to a normal, although 'buffered', state. Since our brain assays were performed on the 21st day, it is difficult to say if the small, although significant, 20% increases in 5-HT levels represent a phase in the gradual return from increased to normal levels, or if it reflects the attainment of steady higher baseline levels.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding possible participation o f presynaptic mechanisms in the lithium action, short-term treatment with lithium was reported to potentiate the tryptophan uptake and the 5-HT synthesis [Knapp and Mandell, 1973], and to cause 5-HT superactivity syndromes in rats [Grahame-Smith and Green, 1974], It has been suggested recently that the head twitches (head shakes or 'wet dog shakes') induced by the admin istration o f 5-HT precursors or 5-HT agonists in the rats are mediated by 5-HT2 receptors [Peroutka et al, 1981;Lucki et al, 1984], On the basis o f these and other reported findings, the present study was carried out to obtain further informa tion about the mechanism o f the lithium action. The effects o f lithium treatment o f rats on 5-HT receptor bindings, 5-hydroxytryptophan (5-HTP)-induced head twitches and the 5-HT turnover were investigated in rats.…”
mentioning
confidence: 99%
“…The effect of chlorimipramine was analysed by the Student's t test: *P < 0.05; **P < 0.001. Table 4 The effect of chlorimipramine in vitro (4 x 10-7 M) on the synaptosomal uptake of 5-hydroxytryptamine (5-HT) in the presence or absence of Li' in the incubation medium 5-HT uptake (pmol/mg protein) Control Lithium preted as being due to an increase in the synthesis and turnover of 5-HT (Knapp & Mandell, 1973;Poitou, Guerinot & Bohoun, 1974). Treatment with Li' for 10 days or more appears to have little effect on turnover (Bliss & Ailion, 1970;Knapp & Mandell, 1973), and it has been suggested that the increase in 5-HIAA following 10 day Li+ treatment may result in part from an impairment of the storage mechanism within 5-HT terminals (Collard & Roberts, 1977).…”
Section: Discussionmentioning
confidence: 99%